2022
DOI: 10.1161/strokeaha.121.037768
|View full text |Cite
|
Sign up to set email alerts
|

Eight-Year Depressive Symptom Trajectories and Incident Stroke: A 10-Year Follow-Up of the HRS (Health and Retirement Study)

Abstract: Background: Evidence suggests a link between depressive symptoms and risk of subsequent stroke. However, most studies assess depressive symptoms at only one timepoint, with few examining this relationship using repeatedly measured depressive symptoms. This study aimed to examine the relationship between depressive symptom trajectories and risk of incident stroke. Methods: This prospective cohort included 12 520 US individuals aged ≥50 years enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…Another study reported six distinct trajectories (Liang et al, 2011). In contrast to Soh et al (2022), we did not identify a fluctuating depressive symptom trajectory. These discrepancies could be attributed to differences in study design (e.g., sample size, statistical approach, or study duration) and research contexts.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Another study reported six distinct trajectories (Liang et al, 2011). In contrast to Soh et al (2022), we did not identify a fluctuating depressive symptom trajectory. These discrepancies could be attributed to differences in study design (e.g., sample size, statistical approach, or study duration) and research contexts.…”
Section: Discussioncontrasting
confidence: 99%
“…At each wave, about 20,000 nationally representative older adult respondents were recruited, with oversamples from Black and Hispanic households and Florida residents (HRS, 2021). HRS respondents are primarily community-dwelling older adults (Sonnega et al, 2014) and their data have been used widely to investigate depressive symptom trajectories among older Americans (Hybels et al, 2016; Liang et al, 2011; Soh et al, 2022; Xiang & Cheng, 2019), providing important implications for clinical psychological intervention targeted at community-dwelling older adults.…”
Section: Methodsmentioning
confidence: 99%
“…Further details on the definitions of these covariates can be found in Additional file 1 : Appendix. S1 [ 31 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Depression and depressive symptoms are associated with a high risk of stroke, especially the repeated occurrences of depressive symptoms [53]. The biological mechanisms include neuroendocrine dysregulation which is characterized by the activation of sympathetic nervous system, dysregulation of the hypothalamic pituitary adrenocortical axis, neurotransmitter-mediated platelet aggregation dysfunction, and immunologic/inflammatory factors [54].…”
Section: Other Factors Influencing the Usage Of Antidepressant In Strokementioning
confidence: 99%
“…This factor may be one of the reasons that antidepressants are not promoting to the recovery of stroke. Developing depressive symptoms or long-term high depression symptoms may indicate the occurrence of cerebrovascular events in the future, suggesting a possible role for antidepressant in stroke prevention [53]. Therefore, antidepressants are of great significance for the prevention and treatment of stroke.…”
Section: Other Factors Influencing the Usage Of Antidepressant In Strokementioning
confidence: 99%